Analysis of the Effect of Service Quality, Price, and Location on Customer Satisfaction at JJ Welding Workshop in Medan City - Tia Murnila; Yana Diana; Husni Muharam Ritonga (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Competition in the business world today is increasingly fierce. This is also felt business people in the welding workshop services sector. The sampling method used is Incidental Sampling Method. The sample in this study was 34 people customers from the JJ Welding Workshop in Medan City and then an analysis was carried out on data obtained using quantitative data analysis. Analysis Quantitative includes: validity and reliability tests, classical assumption tests, regression analysis multiplex, hypothesis testing via t test and F test, and coefficient analysis determination. The results of this scientific research: Service Quality, Price and Location simultaneously have a positive and significant effect on customer satisfaction at the JJ Welding Workshop in Medan City.